Increasing washing performance of wet-spun fibers. Issue 3 (6th June 2016) - Akdere, Musa; Schriever, Sascha; Seide, Gunnar; Gries, Thomas
Abstract : Purpose: – The wet-spinning process is very important for the development and production of new lightweight design materials. The washing process is determined as one of the most cost-expensive part of wet spinning. The purpose of this paper is to show the development of a new washing concept. It proposes to increase the washing performance by decreasing fiber-fiber-interfaces during the washing process. Design/methodology/approach: – For this purpose, conventional washing concepts are investigated by means of simulations and experiments to obtain process knowledge. Computational fluid dynamics simulation and particle image velocimetry measurements are used to investigate the process. Findings: – The overall deficit in conventional washing methods is the large number of fiber-fiber-interfaces, which inhibit the solvent transport out of the compact fiber bundle. Therefore, a new washing concept with included water nozzles is developed. Based on the simulations and observations it is found that the arrangement of the nozzles has direct influence on the fanning of the fiber bundle. Originality/value: – With increased fanning of the fiber bundle a more efficient solvent transport is expected. The developed washing box is a prosperous concept to achieve a higher washing performance during the wet-spinning process. The variable design of the washing box makes it possible to test different nozzle configurations and designs. In this paper the two most promising nozzle arrangements are shown and compared to each other.